2016
DOI: 10.1242/dev.136440
|View full text |Cite
|
Sign up to set email alerts
|

RASGRF2 controls nuclear migration in postnatal retinal cone photoreceptors

Abstract: Detailed immunocytochemical analyses comparing wild-type (WT), GRF1-knockout (KO), GRF2-KO and GRF1/2 double-knockout (DKO) mouse retinas uncovered the specific accumulation of misplaced, 'ectopic' cone photoreceptor nuclei in the photoreceptor segment (PS) area of retinas from GRF2-KO and GRF1/2-DKO, but not of WT or GRF1-KO mice. Localization of ectopic nuclei in the PS area of GRF2-depleted retinas occurred postnatally and peaked between postnatal day (P)11 and P15. Mechanistically, the generation of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…While postmitotic movements of cone nuclei have been reported in mice, the signals and molecular pathways controlling this process have not been resolved [38,39]. A study of ectopically located cones in GRF2-KO mice suggested a potential role for GRF2 and CDC42 in the formation/structure of PARcontaining, polarity-related macromolecular complexes [40,41], and the serine/threonine kinase LKB1 as well as one of its substrates, AMPK, have also been identified as regulators of cone nuclear positioning [42]. Our observations suggest that in human retinae apical cones extend processes basally, prior to relocation, in an active process rather than one based on simple somal displacement by newly generated rods.…”
Section: Discussionmentioning
confidence: 99%
“…While postmitotic movements of cone nuclei have been reported in mice, the signals and molecular pathways controlling this process have not been resolved [38,39]. A study of ectopically located cones in GRF2-KO mice suggested a potential role for GRF2 and CDC42 in the formation/structure of PARcontaining, polarity-related macromolecular complexes [40,41], and the serine/threonine kinase LKB1 as well as one of its substrates, AMPK, have also been identified as regulators of cone nuclear positioning [42]. Our observations suggest that in human retinae apical cones extend processes basally, prior to relocation, in an active process rather than one based on simple somal displacement by newly generated rods.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, RasGrf2 KO mice show lower levels of ERK activation upon NMDA-induction and defective LTP in the CA1 region of the hippocampus (Feig 2011). Additionally, RasGrf2 has also been shown to be important for development of LTP and survival of newborn neurons in the dentate girus (Darcy et al 2014b), for morphogenesis of the retina (Jimeno et al 2016) and for the control of dopaminergic and noradrenergic responses to alcohol (Stacey et al 2012).…”
Section: Rasgrf2mentioning
confidence: 99%
“…During development, all retinal neurons are born apically and then migrate to their final retinal layer where they elaborate and make connections (Baye and Link, 2008). For cones, whose nuclei are arranged at the apical side of the ONL, it is known that their nuclear position can be influenced by either knocking out RASGRF2 the GEF for the Ras/Rho/Rac family of small GTPases (Jimeno et al, 2016), altering dopamine signaling through the D4 receptor (Tufford et al, 2018), or uncoupling the nucleus from microtubules (Yu et al, 2011; Razafsky et al, 2012). Less is known about how rod nuclear position is determined, but microtubule coupling to the nucleus is important.…”
Section: Introductionmentioning
confidence: 99%